Perancangan Aplikasi Sistem Informasi Geotrack Administrasi Surat Berbasis Website - Stepanus Pande Abednigo; Anita Muliawati; Bambang Tri Wahyono (Teknik Informatika Universitas Pamulang, 2020)
This research was conducted to find out how the management process that covers sending sample letters and follow-up letter dispositions at PT Aneka Tambang Tbk's work unit, Geomin Unit to improve the effectiveness of inter-work unit coordination. This research is also motivated by the problem of an ineffective system that monitors the progress of sample analysis. Because in its development, coordination between the laboratory and the team is carried out not computerized. Coordination is not computerized by contacting the relevant parties via private chat, telephone or email. In designing this application using the Waterfall method. The programming languages are HTML and PHP. For Framework using Bootstrap, and for the database using MySQL. Supporting applications used are XAMPP, Sublime Text, and PhpMyAdmin. The final result of this research is a website-based monitoring and tracking application for mail management. It can be concluded that the design of this application provides many benefits in the process of managing letter data, especially in PT Aneka Tambang Tbk, Geomin Unit.